Child Welfare Reform in Bulgaria – from Institutional to Family-Based Community Care: Engaging with Families, Children and Colleagues? - Markova, G; Manolova, H; Hristova, M (Journal of Intellectual Disability - Diagnosis and Treatment, 2018)
The authors present the child welfare policy reform and the process of deinstitutionalization of children’s services in Bulgaria. These developments are examined in the context of the country’s transition from a post-totalitarian to a liberal democratic state and from collectivistic to individual-centred practices. Therefore, the implementation of social policy promoting and regulating individualised community-based services faces challenges related to attitudes that support group-oriented and institutional-based care. There are three key contextual barriers to the provision of quality services for children with disability: engaging with the individual client, involving parents, and working in multidisciplinary teams. Clinical social work vignettes are presented to illustrate the above challenges.